2015
DOI: 10.1007/s10560-015-0418-0
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Personal Transformation for Adolescents Practicing Mindfulness Skills in an Alternative School Setting

Abstract: This qualitative study examined the experiences of alternative school students as they participated in a mindfulness skills program. A 7-month school-based mindfulness skills program was integrated into the Grade 10 curriculum for high school students (N = 19; 10 boys and 9 girls, ages 15-17). Students engaged in mindfulness practices twice weekly during class time. Students practiced breath awareness, and seated, walking, and lying mindfulness meditation during the course of the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Accordingly, mindfulness practice can provide a continuation or acceleration of this natural shift in perspective. Increasing clarity and objectivity about internal experiences may play a pivotal role in leading to reperceiving, and ultimately to positive change and growth (Wisner & Starzec, 2016). Our findings seem to be consistent with this view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, mindfulness practice can provide a continuation or acceleration of this natural shift in perspective. Increasing clarity and objectivity about internal experiences may play a pivotal role in leading to reperceiving, and ultimately to positive change and growth (Wisner & Starzec, 2016). Our findings seem to be consistent with this view.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, self-awareness seems to be rooted in personal growth. Wisner and Starzec (2016) showed that the process of personal transformation for adolescents practicing mindfulness skills occurred through self-awareness (i.e., observing the self through attention) and cognitive, emotional, and behavioral self-regulation. Shapiro et al (2006) proposed a model of mindfulness that identifies the potential mechanisms leading to positive change.…”
Section: Control Groupmentioning
confidence: 99%
“…Mindfulness training for secondary school students with emotional/behavioural issues has resulted in improving their personal skills (Wisner & Starzec, 2016). The students experienced improvements in self-awareness, self-regulation of emotions and behaviour, trusting, and relationships with others.…”
Section: Effectivenessmentioning
confidence: 99%
“…A neurological study of adults shows that regular practice of meditation may have a protective effect on nerves and reduce the decline of cognitive ability caused by normal aging ( Pagnoni and Cekic, 2007 ). The research on mindfulness meditation practice of high school students suggested that meditation has intrinsic perceived benefits, which can help youth change their thoughts, behaviors, and emotions ( Wisner and Starzec, 2016 ). Previous studies of adults using meditation have shown that participating in short-term meditation programs can improve executive function and cognitive efficiency in different areas of the brain on attentional tasks ( Bueno et al, 2015 ; Taren et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%